2014
DOI: 10.1037/cou0000038
|View full text |Cite
|
Sign up to set email alerts
|

Male Asian international students’ perceived racial discrimination, masculine identity, and subjective masculinity stress: A moderated mediation model.

Abstract: This study examined male Asian international college students' perceptions of racial discrimination, subjective masculinity stress, centrality of masculine identity, and psychological distress by testing a moderated mediation model. Participants were 160 male Asian international college students from 2 large public universities. Participants' perceived racial discrimination was positively related to their subjective masculinity stress only at high (but not low) levels of masculine identity centrality. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 63 publications
1
57
1
Order By: Relevance
“…This misguided belief suggests that the responsibilities for adapting to a host culture is a burden that international students must address alone, often without institutional support (Bevis, 2002). Meanwhile, students from Western and English-speaking countries report minimal to no discrimination (Bordoloi, 2014;Bradley, 2000;Constantine et al, 2005;DiAngelo, 2006;Lee & Rice, 2007;Poyrazli et al, 2001;Yeh & Inose, 2003;Wong et al, 2014). International students of color report experiences of racial bias and discrimination due to distinct phenotypical characteristics, English accents, nationality, international student status, and religion.…”
Section: Racial Experiences Of International Students In the United Smentioning
confidence: 99%
“…This misguided belief suggests that the responsibilities for adapting to a host culture is a burden that international students must address alone, often without institutional support (Bevis, 2002). Meanwhile, students from Western and English-speaking countries report minimal to no discrimination (Bordoloi, 2014;Bradley, 2000;Constantine et al, 2005;DiAngelo, 2006;Lee & Rice, 2007;Poyrazli et al, 2001;Yeh & Inose, 2003;Wong et al, 2014). International students of color report experiences of racial bias and discrimination due to distinct phenotypical characteristics, English accents, nationality, international student status, and religion.…”
Section: Racial Experiences Of International Students In the United Smentioning
confidence: 99%
“…We further tested some alternative models, a recommended process when using moderated mediation analyses [38,55]. First, using Model 1 [45], domestic gender role beliefs did not significantly moderate the relationship between somatic amplification at time 1 and pain interference a time 2 (B ¼ -0.049, P ¼ 0.354, 95% CI ¼ -0.151 to 0.054).…”
Section: Post Hoc Alternative Modelsmentioning
confidence: 99%
“…Related to the performances of educational dominance mentioned in the previous section, it is possible to see hostile sexism in the social sphere as a defensive response from men accustomed to topping the ranks. Broader 'widening participation' agendas in higher education may also be pertinent, since extant laddism often incorporates classism and racism as well (Wong et al 2014).…”
Section: Laddism In Social Spacementioning
confidence: 99%
“…This principle should be foundational to our theorisation of masculinities, and we should also attempt to develop from two-dimensional into more multi-dimensional applications. In the US, masculinity has largely been studied as it intersects with race (see for example Jenkins 2012, Goff et al 2012, McGuire et al 2014, Romo 2014, Wong et al 2014. In the UK, the second part of the equation has often been social class (see for example Willis 1977, Williams et al 2008, Stahl 2015, although Mills (2014) has identified a 'washing out' of class in recent studies which tend to focus on the cultural rather than the socio-economic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation